2016
DOI: 10.1515/plc-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Only Cheap Talk after All? New Experimental Psychological Findings on the Role of Verbal Proficiency in Mate Choice

Abstract: Recent evolutionary experimental psychological research found that high verbal proficiency (VP) increased the perceived attractiveness of individuals (more so for males than females), especially in the context of a long-term relationship. Our study had the objective of replicating and extending this research. Similar to previous studies, audio files in which speakers performed scripted self-presentations that had equal content but varied on VP were used as stimuli for opposite-sex participants. VP was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(54 reference statements)
0
8
0
4
Order By: Relevance
“…It is more notable that the results showing greater variance among males corroborate findings regarding the evolutionary psychology of sex differences in general and the evolution of language in particular. From an evolutionary perspective, it can be assumed that a greater phenotypic variance among males than among females mirrors the larger reproductive variance in males compared to females (Archer & Mehdikhani, 2003; Lange, 2012; Lange, Zaretsky, Schwarz, & Euler, 2014). Sex differences in variance have been reported for somatic traits as well (Lehre, Lehre, Laake, & Danbolt, 2008), which also undermines explanations citing environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is more notable that the results showing greater variance among males corroborate findings regarding the evolutionary psychology of sex differences in general and the evolution of language in particular. From an evolutionary perspective, it can be assumed that a greater phenotypic variance among males than among females mirrors the larger reproductive variance in males compared to females (Archer & Mehdikhani, 2003; Lange, 2012; Lange, Zaretsky, Schwarz, & Euler, 2014). Sex differences in variance have been reported for somatic traits as well (Lehre, Lehre, Laake, & Danbolt, 2008), which also undermines explanations citing environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…As emphasized above, communication only by means of single words is even more limited than communicating through written texts. Still, those single words might communicate crucial information (Lange et al, 2016a). In accordance with findings on mate choice in "real life, " Whitty and Buchanan (2010) found that women were more attracted to online user names (hereinafter called nicknames) (e.g., in terms of the motivation to contact the person behind the name) that signaled intelligence, while men were more attracted to nicknames indicative of physical attractiveness.…”
Section: Introductionmentioning
confidence: 76%
“…This research has, on the one hand, identified several characteristics that both sexes prefer in a mate (e.g., healthy), as well as those that are more preferred by women (e.g., good earning capacity, college graduate) and those more preferred by men (e.g., physically attractive) (Buss et al, 1990). The role of language in human mate choice has also been examined recently (e.g., Lange et al, 2014Lange et al, , 2016a. On the other hand, empirical mate choice research has documented that women are more exacting in mate choice decisions, while men face stronger same-sex competition (for an overview, see Buss, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…eloquent sich die Nachrichtensprache darstellt. Sprachniveau wird hierbei als wertfreier Begriff verstanden, der sich als (partiell) synonym zu sprachlicher Gewandtheit sowie Eloquenz auffassen und sich u. a. über Wortschatzdiversität (Anteil unterschiedlicher Wörter), Wortkomplexität (grob: Länge der Wörter) und Satzkomplexität (grob: Länge der Sätze) definieren lässt (s. Lange, 2012;Lange, 2016;Lange, Hennighausen, Brill & Schwab, 2016;Lange, Bögemann & Zaretsky, 2017; s. dazu auch weiter u.). Die bei-den dabei wesentlich verfolgten Fragen lauteten: Ist die Nachrichtensprache eher elaboriert oder eher einfach und schlicht?…”
Section: Nachrichten Und Ihre Sprachlicheunclassified
“…Im Folgenden soll nochmals kurz elaboriert werden, wie Sprachniveau definiert ist und mittels der oben bereits kurz genannten linguistischen Marker operationalisiert werden kann. Sprachniveau (Synonym: sprachliche Gewandtheit; Lange, 2012;Lange et al, 2016Lange et al, , 2017Lange et al, , 2019 ist grob u. a. mittels Wortschatzdiversität (Anteil unterschiedlicher Wörter), Wortkomplexität (Länge der Wörter) und Satzkomplexität (Länge der Sätze) definier-und operationalisierbar. Mehrere Rezeptionsstudien (Lange, 2012;Lange, Zaretsky, Schwarz & Euler, 2014;Lange et al, 2016) bestätigen die Validität dieses Ansatzes: Unterschiedlich sprachlich gewandte Stimuli (Text, Audio, Video), die auf Basis dieser Definition erstellt wurden, wurden von Probanden mit hoher Effektstärke als unterschiedlich sprachlich gewandt bewertet.…”
Section: Instrumente Undunclassified